The Resiliency of the High‐Yield Bond Market: The LTV Default - MA, CHRISTOPHER K.; RAO, RAMESH P.; PETERSON, RICHARD L. (Journal of Finance, 1989)
ABSTRACT This paper investigates the resiliency of the new‐issue high‐yield bond market by examining the changes in implied default rates of such bonds before and after the largest high‐yield bond default, i.e., the LTV bankruptcy. Specifically, the paper compares implied default probabilities of high‐yield bonds during the post‐LTV period calculated from actual new‐issue yields with instrumental default probabilities calculated on the assumption that the default had not occurred. A comparison of these probabilities reveals that the market's perception of default on the high risk segment of the bond market increased significantly after the LTV bankruptcy. However, the effect was transitory, lasting only six months. Thus, the market was resilient to a major default.